Understanding on Train Driver Behaviours Using On-Train Data Recorder (OTDR) - Razali, Nurul Husna; Md Jalil, Mohd Azlis Sani; Ngali, Mohd Zamani (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The rail transportation has been an important role in providing alternative transport to connect to work, families and social activities. In Malaysia, the largest rail company is Keretapi Tanah Melayu (KTMB) that provides plenty type of services which are ETS, KTM Intercity, KTM Komuter etc. This study focuses on the train driver behaviours using On-Train Data Recorder (OTDR). At first, OTDR are used for train fault and management only but based on the previous research, it also stated that it may have the application on monitoring the train driver activities. Train driver’s behaviour is the actions of a train driver to ensure safety in driving the train. Too many actions will lead to human error that will affect the safety and efficiency of the train services. The objectives of this study are to pre-process the raw data and to understand the train driver behaviours. This study focuses on the analysis of the train driver behaviour using OTDR given by ETS KTMB services (Coach 105). The method used was by using the MATLAB software to present the data into the understandable form. Overall, this study can be concluded that train driver behaviours correlated with their actions.